Lagunamide family: total synthesis efforts, final structural determination, new family identification, and biological evaluation - Perera, Kongahapathirage Dona Shashika Sevvandi (Kansas State University, 2024)
Lagunamide C (LagC) is a cyclic depsipeptide isolated by Tan and co-workers from the cyanobacterium Lyngbya majsucle from the western lagoon of Singapore in 2011. It exhibits potent cytotoxicity against a panel of cancer cell lines in low nanomolar concentrations: lymphoma (P388, IC₅₀ 24.4 nM), lung (A549, IC₅₀ 2.4 nM), prostate (PC3, IC₅₀ 2.6 nM), colon (HCT8, IC₅₀ 2.1 nM), and ovarian (SK-OV3, IC₅₀ 4.5 nM). LagC displays significant antimalarial activity with an IC₅₀ of 0.29 μM towards Plasmodium falciparum and weak anti-swarming activity towards Pseudomonas aeruginosa PA01 at 100 ppm. Numerous stereocenters of LagC are in question, as is some additional structural concerns. As such, our lab has proposed a structure LagC and no total synthesis of this proposed structure of this potent bioactive agent has been reported. While LagC, our proposed structure, has not been synthesized, Lag A & B have been. The extra methylene unit present within the polyketide unit of LagC makes it the only 27 membered macrocycle of the whole aurilide family and limits the utility of the routes to the polyketide units of LagA/B. This dissertation work discloses an improved, scalable, and efficient synthetic route to access the polyketide unit of LagC diastereoselectively, final macrocyclization and ring closing metathesis attempts to access the 27 membered ring of LagC, and efforts in its final structural elucidation. Synthesis of 27 membered aurlide macrocycle analogs, their biological evaluations, and a new proposed mode of action for LagC and its family of natural products is deliberated. Furthermore, based upon the recent discovery of LagD, a methyl truncate variant of LagA, our lab has undergone a synthesis of the proposed natural product LagE based on the same methyl truncation. Synthetic efforts and biological identification of this proposed natural product is also discussed.
Keywords: Lagunamide; Total synthesis; Structure elucidation; Polyketide synthesis; Macrocyclization